Comparison of TAP block and epidural analgesia for postoperative analgesia after robotic-assisted radical prostatectomy - O.O. Volkov; Lutsenko V.V.; M.O. Plis; M.V. Pavlenko; Krishtafor D.A. (Medičnì Perspektivi)
Pain remains an important problem after radical prostatectomy, leading to discomfort and sometimes prolonged hospital stays. Despite the fact that laparoscopic procedures are less invasive surgical interventions, they can still be challenging in terms of postoperative pain, as both somatic and visceral pain pathways are involved. To alleviate pain and optimize improved recovery after laparoscopic prostatectomy, regional anesthesia techniques have been used to avoid or reduce the need for opioids. The aim of our study was to investigate the postoperative recovery of patients after laparoscopic robotic-assisted radical prostatectomy, depending on the method of postoperative analgesia and in the context of the peculiarities of anesthesia in robotic surgery. To achieve this goal, the “Medical Plaza” Medical Center examined 49 patients who underwent radical prostatectomy using a robotic system. Patients were divided into 2 groups. Group 1 (n=25) – combined intraoperative anesthesia with epidural analgesia with 0.125% bupivacaine. Patients in group 2 (n=24) underwent TAP-block with 15 ml of 0.25% bupivacaine immediately after the last suture was placed on the skin both sides of the abdomen. Patients in the groups did not differ in age, height, body weight and physiological status (р>0.05) according to the American Society of Anesthesiologists (ASA) scale. When analyzing the statistical data it was found that the volume of the prostate did not differ in the study groups, as well as the duration of the operation and the amount of blood loss (р>0.05). Blood pressure and heart rate fluctuations were similar between the groups. The amount of muscle relaxants used had no statistical difference in the study groups (р>0.05). The amount of opiates used during anesthesia did not differ (р>0.05). Mobilization of patients in both groups occurred in 8 hours without statistical difference (p=0.094). A direct medium strength significant correlation was found between the method of analgesia and weakness in one of the lower limbs at the time of mobilization (r=0.69; p=0.039), a direct medium strength significant correlation was found between the size of the prostate and the time to tracheal extubation (r=0.39; p=0.041). So, the level of intraoperative blood loss did not depend on the variants of perioperative analgesia. Haemodynamics and heart rate did not decrease with the addition of intraoperative epidural analgesia. Intraoperative initiation of epidural analgesia with a low concentration of local anesthetic does not affect the rate of postoperative mobilization. Pain after robotic radical prostatectomy is moderate, but requires multimodal treatment for faster mobilization of the patient, adaptation to the existing urinary catheter. Both epidural analgesia and TAP block have shown sufficient safety profile and efficacy in postoperative pain management. After radical prostatectomy, the TAP-block is an effective method of analgesia, while not interfering with the timely full mobilization of the patient. Epidural analgesia has a high analgesic profile, but is associated with certain risks of catheter migration and interference with full mobilization of the patient.